2021
DOI: 10.3201/eid2711.211144
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Vibrio cholerae O1 Sequence Type 75, South Africa, 2018–2020

Abstract: We describe the molecular epidemiology of cholera in South Africa during 2018-2020. Vibrio cholerae O1 sequence type (ST) 75 recently emerged and became more prevalent than the V. cholerae O1 biotype El Tor pandemic clone. ST75 isolates were found across large spatial and temporal distances, suggesting local ST75 spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Remarkably, Iraq pre-7PET ST71, strain Vc_NCTC5395_1938 and other recently isolated clinical and environmental ST71, ST75, and ST169 epidemic lineage 3 strains from South Africa, Thailand, and China shared a MRCA and dated to 1929 (95% HPD interval, 1914 to 1937). Based on our study, there were multiple transmission events that occurred prior to outbreaks in South Africa caused by ST75 strains in 2018 to 2020 ( 26 ) and in China caused by ST169 strains in 2001 to 2009 ( 27 ) ( Fig. 2 and 4 ).…”
Section: Resultsmentioning
confidence: 81%
“…Remarkably, Iraq pre-7PET ST71, strain Vc_NCTC5395_1938 and other recently isolated clinical and environmental ST71, ST75, and ST169 epidemic lineage 3 strains from South Africa, Thailand, and China shared a MRCA and dated to 1929 (95% HPD interval, 1914 to 1937). Based on our study, there were multiple transmission events that occurred prior to outbreaks in South Africa caused by ST75 strains in 2018 to 2020 ( 26 ) and in China caused by ST169 strains in 2001 to 2009 ( 27 ) ( Fig. 2 and 4 ).…”
Section: Resultsmentioning
confidence: 81%
“…The qnrVC4 gene (Quinolone resistance pentapeptide repeat protein QnrVC4) was detected in all three ST579 strains. This gene has also been found in quinolone-susceptible strains of ST75 (SLV of ST579) in South Africa [ 38 ]. This gene, different alleles of which are located in a chromosomal super-integron, is not necessarily related to resistance as indicated here and in several previous studies [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with previous report on clinical V. cholerae O1 isolated from an urban community in Dhaka, which also belonged to ST69 [ 32 ]. Recent studies in Asia and Africa also reported that the majority of the seventh pandemic El Tor (7PET) V. cholerae O1 strains belongs to ST69 [ 33 , 34 ]. It corroborates the observation that the recent epidemic cholera outbreak in Dhaka is predominantly caused by the 7PET lineage, although further study is needed to confirm the clonal relatedness of V. cholerae strains responsible for endemic cholera in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%